The Nurse’s Caring Behavior on Multicultural Hospital Settings: A Literature Review - Ulfiatun Hasanah; Nurfika Asmaningrum; Kholid Rosyidi Muhammad Nur (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2021)
Introduction: Cultural diversity means a different ethnic group in a country or region; these conditions bring different beliefs and understandings to health care and has an impact on the caring behaviour of nurses. Objective: To describe caring behaviour of nurses on patients in multicultural settings in hospitals. Methods: A Literature review and used 5 comprehensive electronic databases such as Google Scholar, PubMed, Science Direct, ProQuest and Garuda. Results: 10 articles used in this research, 3 themes were analysed, including: forms, barriers, and nursing care strategies for multicultural patients. Forms of nurse caring such as understanding and focus on patient, cultural sensitivity, and verbal and non-verbal communication. The caring barriers were ethnocentrism, conflicting perceptions, lack of cultural knowledge, language differences, inadequate hospital facilities, religious differences, patient family behaviour, ineffective coping, and body exposure. The strategies were providing translators, increasing education, organizational support, and improving coping strategies. Conclusion: The researcher concludes that when nurses do caring, they must pay close attention to the culture of the patient, and the strategies found in this study can be used to reduce the barriers that occur while nurses were caring for multicultural patients so that the patient does not feel different during health care.